The assessment algorithm for sustainable development goals in the Hukiv, Dereluy, and Vyzhenka river basin systems of Chernivtsi oblast - Kyryliuk, Serhii (My University, 2021)
The study deals with an integral assessment of hydromorphological and geoecological conditions of the Hukiv (flatland type of river), Dereluy (foothill type of river), and Vyzhenka (mountainious type of river) river basin systems. The indicators characterizing the river basin in the best way as a holistic system, the channel, floodplain, and watershed altogether, in natural reference conditions and in terms of human economic activity are addressed. The assessment hydromorphological test and geoecological monitoring of small rivers (SWOT-analysis) in accordance with the developed universal algorithm for hydromorphological assessment of small river basins for the sustainable development goals are generated and fulfilled. Interpretation maps for the sustainable development of the Hukiv, Dereluy and Vyzhenka rivers are created. The practical importance and relevance concerns the potential application of the proposed monitoring and the algorithm to solve methodological and applied problems related to the functioning of the systems “basin–river–human” and “basin–river–riverbed” in terms of modern human activity and needs; the need to modify consumer-type stereotypes for the use of natural resources, as well as to provide recommendations for enhancing the resource-efficient and sustainable activities in basin systems and small rivers.
Keywords: hydromorphological quality, sustainable development, riverbed, floodplain, anthropogenic influence